IMPLEMENTASI PERAN KOMITE SEKOLAH DALAM PELAKSANAAN MANAJEMEN BERBASIS SEKOLAH DI SMA NEGERI 1 BAKAUHENI LAMPUNG SELATAN - Hasanudin (UNISAN JURNAL, 2022)
The purpose of this study is to determine the implementation of strategic planning in improving the quality of educators. To answer the research problem, this type of field research is used. Data collection techniques in this study include: observation, interviews, and documentation. The data were analyzed, namely data reduction, data presentation, and data verification or drawing conclusions. Then tested the validity of the data by using triangulation of sources and research techniques. The conclusion from the results of this study is that the implementation of strategic planning at SMA Negri 1 Bakauheni is good, including the implementation of strategic planning at SMA Negri 1 Bakauheni. In the strategic planning step, the head of the Sekcool takes several steps, namely strategic planning, strategic planning, and strategic planning evaluation. The head of the Sekolah carried out several planning steps, namely forming a special team as the initiator of the strategic planning from various qualified resources, dividing groups with their respective tasks; identify and review various laws and regulations and sekcool policies regarding improving the quality of educators; creating the vision, mission, and values of the ma drasa; analyze by identifying the strengths, weaknesses, strengths, and threats contained in SMA Negri 1 Bakauheni according to the actual conditions in the ma drasa. This activity is assisted by a team formed; identify the strategic issues at hand. At this step strategic issues have not been analyzed according to the level of urgency; formulating strategies to ma nage issues by formulating planned programs and activities to address strategic issues; as well as reviewing and adopting the strategies set out in the strategic plan.